MANAJEMEN PAKAN SAPI POTONG DI ADHI FARM KARANGANYAR, JAWA TENGAH - , RIZALLUDIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One way to overcome the shortage of meat in the country is increasing the productivity of livestock, such as beef cattle. Beef cattle in the world there are aspects that affect the productivity of livestock, one of the feed management. Field practice activities conducted in beef cattle Adhi Farm, Karanganyar, Central Java. Activity lasted for 6 days, from March 17 to 22 March 2014. The purpose of field practice is to determine the management of beef cattle feed in Adhi Farm. Information gathering is done by direct observation and interviews to employees Adhi Farm. Results of field practice is to know the management at Adhi Farm cattle feed such as: Feed: Elephant grass and forage in the form of fermented rice straw. Concentrate consisting of: corn flour, rice bran, soybean meal, coffee skin. Feeding Time: Morning, forage at 08.00 am, 09.00 pm and concentrate noon: 13:00 pm forage, concentrate at 14.00 pm. The number of feeding: age 4-18 months: 1 kg of elephant grass, straw fermentation 3 kg, 1 kg of concentrate. Age 18 months and above: 2 kg of elephant grass, 6 kg of straw fermentation, 3 kg of concentrate. From the observations during field work practice can be concluded that, feed management in Adhi Farm has been good, but not optimal.